Cyphoedma n. gen. now described after a century of use, with the addition of a new species from Central America (Geometridae, Ennominae) - Tanner Alex Matson (Revista Brasileira de Entomologia, 2024)
ABSTRACT Cyphoedma n. gen., is validly described following a century of use as an unpublished manuscript name. Cyphoedma mirafloresa (Dognin, 1892) rev. stat. n. comb. is elevated to full species from subspecific status with Cyphoedma transvolutata (Walker, 1860) n. comb., and a third species in the genus is described from Central America: Cyphoedma ashleyorum n. sp. The adult habitus and male and female genitalia are illustrated for each of the three species and available COI (DNA) barcode data are reviewed.